0400 Habitual Sleep, Circadian Misalignment, and Cardiovascular Risk Factors Among Late Adolescents. (27th May 2020) - Ji, X; Wang, Y; Saylor, J; Patterson, F; Ruggiero, L
Abstract: Introduction: Emerging evidence suggests the potential role of sleep in cardiovascular disease (CVD) risk. Sleep variability and circadian misalignment may represent understudied sleep dimensions, particularly among late adolescents. This study investigated the associations of habitual sleep, circadian misalignment, night-to-night sleep variability with CVD risk factors among late adolescents. Methods: Using a cross-sectional design, we enrolled 58 healthy, college students (19.22±1.06 years old). Participants completed a 7-day sleep diary, the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale. Circadian misalignment was assessed using the weekend-weekday differences in sleep duration and midsleep time. Sleep variability was calculated as intra-individual standard deviation of sleep durations. The number of CVD risk factors (BMI, waist circumference, blood pressure, fasting glucose and lipid profile) above subclinical/clinical thresholds was used as a proxy of overall risk. Logistic and generalized linear regression tested the relationships. Results: Forty-two participants (73%) had at least one elevated CVD risk factors and 19 (34%) were short sleepers (<7 h). On average, the midsleep shifted 54 minutes later on weekends and the intraindividual sleep variability was 1.31 hours. After controlling for age, gender and race, there was a trend towards higher overall CVD risk (β=0.45±0.22, p=0.05) with a greater weekend-weekday discrepancy in sleep duration. For each CVD risk factor, a greater discrepancy in weekend-weekday midsleep times (OR=2.29±0.82, p=0.02) was estimated to increase the odds of high blood pressure. Participants with greater discrepancy in weekday-weekend sleep durations (OR=1.58±0.41, p=0.03) or excessive daytime sleepiness (OR=4.68±3.38, p=0.03) were more likely to have high BMI. Worse sleep quality (higher PSQI scores) was associated with high BMI (OR=1.36±0.19, p=0.03) and waist circumference (OR=1.40±0.24, p=0.04). Conclusion: This study suggests that circadian misalignment, compared with other sleep characteristics, better predicts cardiovascular risk among late adolescents. Future research is needed to examine the interaction among circadian misalignment, sleep variability and sleep duration on CVD risk. Support: American Nurse Foundation 18A01422